Significance of EMG and ENMG in the Diagnosis and Treatment of Degenerative-Dystrophic Diseases of the Spine (Literature Review) - E. G. Ippolitova; T. K. Verkhozina; Z. V. Koshkareva (Acta Biomedica Scientifica)
The article presents the review of domestic and foreign literature on the use of neurophysiological diagnostic methods – electroneuromyography (ENMG) and electromyography (EMG) in degenerative-dystrophic diseases of the spine. The ENMG method is of great importance for theoretical neurology, obtaining new data on the structural and functional organization of the central and peripheral nervous system in the process of individual development. Electromyography as a diagnostic method studies the electrical activity of the peripheral apparatus of the nervous system. With these methods we directly evaluate both voluntary bioelectric activity of muscles at rest and during their activation (EMG), and caused by stimulation (ENMG). Most authors believe that modifications of stimulation electromyography are objective diagnostic methods that allow to assess the functional state of the peripheral nervous system. Interesting is the fact that changes in EMG and ENMG parameters for osteochondrosis of the spine are recorded even in the absence of external manifestations of the disease. At the same time, for patients with myofascial syndrome in lumbar osteochondrosis, a bilateral decrease in the direct and reflex excitability of motoneurons is characteristic, a slowing down of the pulse along the arc of the H-reflex on the side of the pain and a two-sided local acceleration of the pulse on the distal part of the efferent part of the H-reflex arc from the popliteal pits to soleus muscle. Noteworthy is the fact that the pathological process in the nervous tissue according to ENMG in patients with osteochondrosis of the spine with unilateral radicular syndromes is bilateral. The work of our clinic has shown that diagnostic electroneuromyography can be considered as a medical procedure – electropuncture, according to its results, tactics of both surgical and conservative treatment can be determined. Data of EMG and EMG, carried out after the end of any of the listed types of treatment, serve as an objective control of their effectiveness.